Strengthening the Education Sector : Response to HIV/AIDS in the Caribbean - UNESCO; World Bank (Washington, DC : World Bank, 2012)
This report the findings and outcomes of the three joint UNESCO/World Bank missions to Guyana, Jamaica, and St. Lucia, and elaborates on next steps identified for action at both national and regional levels. The report also sets these findings and next steps within the broader context of the Caribbean plan for action and presents in its appendixes sample resources to guide the development of a comprehensive response to Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome (HIV&AIDS) by the education sector. The priority placed on the education sector's response is based on evidence that education contributes towards the knowledge and personal skills essential for the prevention of HIV, and protects individuals, families, communities, institutions, and nations from the impact of AIDS. Education helps to overcome the conditions that facilitate the spread of HIV and can create the understanding and tolerance that contribute to reduced stigma and discrimination against vulnerable and marginalized communities and people living with HIV. The CARICOM regional body in the Caribbean, as well as leadership at the national level, has demonstrated commitment to accelerating the education sector response to HIV&AIDS. To fully maximize efforts at the national and regional levels, including (i) information and research; (ii) capacity building for planning, decision- making and coordination; (iii) strengthening teacher education and learning materials; and (iv) stigma, discrimination and human rights, including attention to cultural differences, will be addressed more systematically.